A manoeuvre warfare analysis of South Africa’s 1914-1915 German South West African campaign - Garcia, Antonio (Scientia Militaria - South African Journal of Military Studies, 2017)
The study reported in this article explored the nexus between military theory and history. Military theory attempts to quantify, qualify and illuminate the often unpredictable phenomenon of war. The article consists of two parts: the theory of manoeuvre warfare and the history of the 1914-1915 South African campaign in German South West Africa (GSWA). The GSWA campaign has been described in many ways as a secondary theatre within the greater geostrategic chess game of the First World War. The objective of this analysis was to question whether the South African victory resulted from vast numerical superiority or from the operational concepts, which the South Africans applied in the execution of the campaign.